REPRESENTATION OF WOMEN IN INDONESIAN HORROR FILMS: A SOCIOLOGICAL ANALYSIS OF GENDER TOWARDS STEREOTYPES AND OBJECTIFICATION: REPRESENTASI PEREMPUAN DALAM FILM HOROR INDONESIA: ANALISIS SOSIOLOGI GENDER TERHADAP STEREOTIPE DAN OBJEKTIFIKASI - Ubaidah Adielah; Imam Tajus Subki; Elias Saiba; Oman Sukmana; Tri Sulistyaningsih (SOSIOEDUKASI, 2025)
The main objective of the research is to present an in-depth analysis of the portrayal of women in Indonesian horror films, with an emphasis on efforts to dismantle stereotypes and objectifications that are commonly found, as well as identify their sociological implications for the construction of gender and power relations. This study adopts the narrative literature review method, a systematic qualitative approach to identify, evaluate, and synthesize findings from previous studies related to the representation of women in Indonesian horror films. The method allows for the compilation of a comprehensive picture of existing scientific discourse, identifying key patterns, and highlighting underexplored areas in the literature. The findings of the study show that the representation of women in Indonesian horror films consistently reflects and reinforces gender stereotypes and objectifications that are deeply rooted in patriarchal societies. This indirectly reflects the socio-cultural values that place women in subordinate positions, as reflected in the patriarchal structure of Indonesian society. While creepy figures, women are often portrayed as having destructive supernatural powers, but they usually appear as a response to injustice or a manifestation of the suffering they experience, rather than as a form of autonomous and positive agency.